ANALISIS PENGARUH ALOKASI ANGGARAN APBD KABUPATEN/KOTA TERHADAP KEMISKINAN di INDONESIA 2006-2009 - , Dimas Ari Darmantyo, S.Pi, Dr. Artidiatun Adji, M.Ec., MA ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This thesis aims to analyze the effect of district/city levels budget allocation in Indonesia for the period 2006-2009. Using panel data of 172 districts/cities, this study found that budget allocation of distr ict/city is not pro-poor, however it has the possibility to reduce the level of poverty at a time. The results also showed low rates of inflation can reduce levels of poverty.